2023
DOI: 10.3390/su151914048
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study of the Effects of Temperature and pH on Lead Bioremoval Using Serratia marcescens

Dafne Lecca-Caballero,
Eyber Vega-Moreno,
Luis Cabanillas-Chirinos
et al.

Abstract: Heavy metal contamination of water is a widespread problem in Peru and represents a potential threat to the ecosystem. Bacteria are an ecological alternative to treating these effluents. This research aims to determine the influence of temperature and pH on the lead (Pb) bioremoval in surface water using Serratia marcescens under laboratory conditions. The sample was collected from a stream located in Santiago de Chuco City (Peru). Treatments (T) were carried out by combining pH (5 and 7) and temperature (25, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, the competition is lost with the reduction of hydrogen ions in intestinal conditions and metal reattachment occurs. This has been observed by Lecca-Caballero et al (2023) in the case of Pb biosorption by Serratia marcescens (Lecca-Caballero et al, 2023). Furthermore, it was suggested that noncovalent electrostatic bonds (e.g., Van der Waals and hydrogen bonds) were formed between heavy metal and yeast (Zoghi et al, 2021).…”
Section: Stability Assessment Of S Cerevisiaeheavy Metal Complexes Fo...mentioning
confidence: 73%
“…However, the competition is lost with the reduction of hydrogen ions in intestinal conditions and metal reattachment occurs. This has been observed by Lecca-Caballero et al (2023) in the case of Pb biosorption by Serratia marcescens (Lecca-Caballero et al, 2023). Furthermore, it was suggested that noncovalent electrostatic bonds (e.g., Van der Waals and hydrogen bonds) were formed between heavy metal and yeast (Zoghi et al, 2021).…”
Section: Stability Assessment Of S Cerevisiaeheavy Metal Complexes Fo...mentioning
confidence: 73%